2012
DOI: 10.1186/2008-2231-20-13
|View full text |Cite
|
Sign up to set email alerts
|

A survey of poison control centers worldwide

Abstract: To stem the rising incidence of toxic exposure as well as the associated morbidity and mortality, the past century has seen the establishment and evolution of poison control centers (PCCs) worldwide. Depending on the location, PCCs vary in terms of staffing model, services offered, and funding sources. In this article, we discuss a survey of poison control centers worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…The past century has seen the development and evolution of PCCs worldwide to decrease morbidity and mortality associated with poisons. Several studies have shown that PCCs are cost effective by reducing the number of ED visits, decreasing the length of hospital stay and improving patient outcomes [18] and a play a vital role in monitoring and ensuring safe use and distribution of antidotes [12]. The WHO has stated that a central depot of antidotes could be effective and economically viable to ensure proper distribution of antidotes.…”
Section: Discussionmentioning
confidence: 99%
“…The past century has seen the development and evolution of PCCs worldwide to decrease morbidity and mortality associated with poisons. Several studies have shown that PCCs are cost effective by reducing the number of ED visits, decreasing the length of hospital stay and improving patient outcomes [18] and a play a vital role in monitoring and ensuring safe use and distribution of antidotes [12]. The WHO has stated that a central depot of antidotes could be effective and economically viable to ensure proper distribution of antidotes.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Should naloxone be given to the comatose tramadol-intoxicated patients? [2,3,18,19] This highlights the role of global act by doing more research to fix the problem of tramadol [20,21]. …”
Section: Letter To the Editormentioning
confidence: 99%
“…The recent published article by Dr. Pourmand and his colleagues under the title of "A survey of poison control centers worldwide" was read eagerly [1]. I have had the opportunity to work for Iran National Drug and Poison Information Center (NDPIC) and also Central Staff of NDPIC for several years.…”
Section: Dear Sirmentioning
confidence: 99%
“…All DPICs must report their activities and statistics to the NDPIC every three months (seasonally) [3]. In Pourmand's article, it was mentioned that there are 29 DPIC in Iran [1], while the current number of active DPICs is 34 now. According to the report of NDPIC, during the year 1390 Khorshidi (21th March 2011 – 20th March 2012) a total of 224368 telephone calls were responded by these 34 DPICs [3], a statistics seeming considerable.…”
Section: Dear Sirmentioning
confidence: 99%